2021
DOI: 10.3390/ani11092660
|View full text |Cite
|
Sign up to set email alerts
|

Training and Validating a Machine Learning Model for the Sensor-Based Monitoring of Lying Behavior in Dairy Cows on Pasture and in the Barn

Abstract: Monitoring systems assist farmers in monitoring the health of dairy cows by predicting behavioral patterns (e.g., lying) and their changes with machine learning models. However, the available systems were developed either for indoors or for pasture and fail to predict the behavior in other locations. Therefore, the goal of our study was to train and evaluate a model for the prediction of lying on a pasture and in the barn. On three farms, 7–11 dairy cows each were equipped with the prototype of the monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…On the contrary, natural and artificial processes exhibit some activity patterns more frequently than others because their daily functioning requires it. Similar situations are encountered when considering wearable systems for livestock activity monitoring [10], human behavior classification [11], gesture recognition [12], as well as room occupancy and activity detection [13].…”
Section: Introductionmentioning
confidence: 76%
“…On the contrary, natural and artificial processes exhibit some activity patterns more frequently than others because their daily functioning requires it. Similar situations are encountered when considering wearable systems for livestock activity monitoring [10], human behavior classification [11], gesture recognition [12], as well as room occupancy and activity detection [13].…”
Section: Introductionmentioning
confidence: 76%
“…Crawling backwards (yes/no) Backwards movement on carpal joints after the head lunge Yes: 71 (13.0%) [21] No: 477 (87.0%) [48] NA: 21 [16] LHL, RFL, LFL sensitivity and specificity (Eq. 1, [50]).…”
Section: Standing Upmentioning
confidence: 99%
“…Sensors, such as accelerometers, are now frequently used to study and monitor cow behavior. From acceleration data, general activities [17][18][19], lying behavior [20,21], grazing and rumination behavior [22][23][24], and health problems such as lameness can be tracked [25,26]. This data gives valuable insight into the welfare and health of animals, and enables farmers, veterinarians, and researchers to make informed decisions [27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, contact sensors (including accelerometers, inertial measurement units (IMU), pedometers, and magnetometers) have usually been designed to collect different behavioral movements and recognize and track animal behaviors [11,19,[34][35][36]. It is reported that wearable behavior-monitoring systems that are integrated with sensors, such as collars, ear tags, and leg bands, have been used to autonomously identify dairy cow behavior while minimizing human interference or human error [12,35,37,38]. Together with the sensors, machine-learning techniques were applied, including various algorithms, such as random forest (RF), decision tree (DT), and K-nearestneighbors (KNN), to classify the different behaviors of cows [36,[38][39][40].…”
Section: Research On Behavioral Recognitionmentioning
confidence: 99%